Exploring Spatialized Audio & Video for Distributed Conversations - Inkpen, Kori; Hegde, Rajesh; Czerwinski, Mary; Zhang, Zhengyou (CSCW 2010, 2010)
Previous work has demonstrated the benefits of spatial audio conferencing over monophonic when listening to a group conversation. In this paper we examined three-way distributed conversations while varying the presence of spatial video and audio. Our results demonstrate significant benefits to adding spatialized video to an audio conference. Specifically, users perceived that the conversations were of higher quality, they were more engaged, and they were better able to keep track of the conversation. In contrast, no significant benefits were found when mono audio was replaced by spatialized audio. The results of this work are important in that they provide strong evidence for continued exploration of spatialized video, and also suggest that the benefits of spatialized audio may have less of an impact when video is also spatialized.